Technologies for harvest and effective use of water in rainfed agricultural areas - Hamada, H.(Japan International Research Center for Agricultural Sciences, Tsukuba, Ibaraki) (JARQ. Japan agricultural research quarterly, 2006)
Agriculture in developing countries usually depends on rainfall. However, erratic rainfall makes agricultural production unstable. It is necessary to harvest water resources and to use them efficiently in order to stabilize crop yields. Methods of harvesting water resources are subject to topography. In lowlands, it is easy to collect water, because water flows in, but this is difficult in uplands, because water flows out. This article reviews methods of harvesting water resources and using them effectively in developing countries by reviewing papers from the last 20 years.